Gender differences in innovation: the role of ambidextrous leadership of the team leads. Issue 7 (17th April 2020) - Zuraik, Abdelrahman; Kelly, Louise; Perkins, Vernita
Abstract : Purpose: This study explores the impact of gender on team leadership style and how it impacts team innovation outcomes using the ambidexterity theory (opening and closing behaviors) of leadership for innovation. Design/methodology/approach: A total of 215 self-report surveys of team members were collected for hypothesis testing. This study tests whether team leader gender moderates the relationship between ambidextrous team leadership and team innovation. Findings: Female team leaders are engaged in less opening behaviors of ideation, risk-taking and exploration than their male counterparts. Additionally, when female leaders engaged in closing behaviors, which include assigning roles and timelines, they had less impact than the closing behaviors of their male colleagues. Female team leaders were perceived as less effective in leading innovation than males. Research limitations/implications: This study examines the influence of gender on team leadership and innovation outcomes. There are drawbacks of cross-sectional data, sample selection issues and potential problems of percept–percept relationships. Practical implications: These findings suggest that female team leads may need greater organizational support and organizational senior leadership support to take risks (opening behavior) to produce greater team innovation and increase leader visibility. Social implications: Society can achieve even greater innovation outcomes by understanding and addressing the unique obstacles woman team leaders face with innovation. Organizations can benefit from innovation and resilience by supporting women team leaders in their diverse delivery of innovation. Originality/value: This is the first study to look at the influence of gender and leadership on team innovation outcomes. Ambidextrous leadership theory provides insights into the specific challenges woman team leaders experience; however, so far no research has addressed the innovation outcome challenges female team leaders encounter. Since innovation and leadership can be a key component of visibility, compensation and promotion, it is necessary to investigate the challenges female team leads face in the innovation process.